A dança no projeto ‘Mais Educação’: problematizando as experiências dançantes em andamento - Cabral, Juliana Carvalho; Finoqueto, Leila Cristiane Pinto; Medina, Berenice Mattos (Revista Didática Sistêmica, 2015)
Não Disponível.